Compensation And Motivation In Improving Employee Performance PT. Romi Violeta Sidoarjo - Hersa Farida Qoriani (CV Putra Publisher, 2022)
Reference to work enthusiasm in improving employee performance applied by PT Romi Violeta. Compensation and motivation need to be given to employees so that they have work enthusiasm and prosperity in order to achieve targets and prosperous employees. The formulation of the problem of this research is: 1) How is the application of compensation to the performance of employees of PT Romi Violeta Sidoarjo. 2) How is the application of motivation on the performance of employees of PT. Romi Violeta Sidoarjo?, 3) What are the implications of applying compensation and motivation to improving the performance of employees of PT. Romi Violeta Sidoarjo. The aims of this study are: 1) To describe the application of compensation to employee performance at PT. Romi Violeta. 2) Describe the application of motivation in PT. Romi Violeta. 3) To describe the implications of applying compensation and motivation to increase work at PT. Romi Violeta. In preparing this thesis, the author uses a qualitative approach research method. This type of research uses a type of field research (field research). The results of this study conclude: The application of compensation carried out by PT. Romi Violeta Sidoarjo to his employees is very kind and appropriate. Compensation provided such as allowances,reward, and others according to regulations. Compensation and motivation are a unit that are interrelated and influence the improvement of employee performance. However, in January–June 2021 PT. Romi Violeta experienced a decrease in employee performance by 5% because some employees considered compensation in the form of bonuses to be inappropriate, but in fact the bonuses given were in accordance with company regulations. Therefore, the company/industry needs to provide another understanding of the bonuses received so that misunderstandings do not occur.